KADAR ANTIBODI IgG SARS COV-2 SETELAH VAKSINASI COVID-19 DOSIS LANJUTAN - Fajrunni'mah, Rizana; Purwanti , Angki; Setiawan, Budi (Poltekkes Kemenkes Bandung, 2023)
COVID-19 is a problem throughout the world, including Indonesia. One of the efforts to overcome the COVID-19 pandemic is vaccination. A follow-up or booster dose was needed to increase individual protection because there was a decrease in antibodies 6 months after receiving vaccination. This study aimed to determine SARS-CoV-2 IgG antibody levels before and after 8 months of the third booster vaccination. This research method was observational with a longitudinal, cohort approach to 27 samples using a consecutive sampling technique at the Health Polytechnic of the Ministry of Health, Jakarta III in April-November 2022. The data collection techniques used questionnaires and venous blood sampling to examine quantitative Anti-SARS CoV-2 Ig G levels using the CMIA (Chemiluminescent microparticle immunoassay) method with the Architect tool which was carried out twice, namely before administration and 8 months after the third booster vaccination with a heterologous vaccine. Data were analyzed using a statistical test of the difference between the means of two groups. Based on the research results, although statistically there was no significant difference between before and 8 months after vaccination (p=0.055), there was a decrease in the mean quantitative Anti-SARS CoV-2 IgG level of 5301.24 AU/mL. As many as 63% of subjects experienced a decrease in antibody levels 8 months after vaccination compared to before the third booster vaccination. Longitudinal studies are needed to determine protective antibody levels.